Polymer encapsulated microcavity optomechanical magnetometer - Jiangang Zhu (Nature Portfolio, 2017)
Abstract We demonstrate a magnetometer using polymer encapsulated whispering-gallery-mode microcavity actuated by a micro-magnet. The magnetic field induces force on the micro-magnet causing deformation in the polymer around the microcavity. Subsequently the microcavity detects the change in the refractive index of the polymer resulted from the deformation. This magnetometer works in the frequency range of hertz-to-kilohertz range and achieves a sensitivity of 880 pT/Hz1/2 at 200 Hz in a micro-scale sensor volume. Polymer encapsulation of the magnetometer and fiber optical connection ensures environmental robustness and practicality of the sensor.